Coproporphyrin III Produced by the Bacterium Glutamicibacter arilaitensis Binds Zinc and Is Upregulated by Fungi in Cheese Rinds - Jessica L. Cleary (American Society for Microbiology, 2018)
ABSTRACT Microbial communities of fermented food microbiomes typically exhibit predictable patterns of microbial succession. However, the biochemical mechanisms that control the diversity and dynamics of these communities are not well described. Interactions between bacteria and fungi may be one mechanism controlling the development of cheese rind microbiomes. This study characterizes a specific bacterium-fungus interaction previously discovered on cheese rinds between the bacterium Glutamicibacter arilaitensis (formerly Arthrobacter arilaitensis) and fungi of the genus Penicillium and identifies the specialized metabolites produced during cocultures. G. arilaitensis was previously shown to produce an unknown pink pigment in response to the presence of Penicillium. Using a combination of mass spectrometry, nuclear magnetic resonance (NMR), and transcriptome sequencing (RNA-seq), we determined that this pigment production is associated with production of coproporphyrin III. The discovery that coproporphyrin III preferentially bound zinc over other trace metals found in cheese curds highlights the value of using analytical chemistry to confirm identity of predicted chemical species. IMPORTANCE Bacterium-fungus interactions play key roles in the assembly of cheese rind microbial communities, but the molecular mechanisms underlying these interactions are poorly characterized. Moreover, millions of people around the world enjoy eating cheeses and cheese rinds, but our understanding of the diversity of microbial metabolites ingested during cheese consumption is limited. The discovery of zinc coproporphyrin III as the cause of pink pigment production by Glutamicibacter arilaitensis suggests that secretion of this molecule is important for microbial acquisition of trace metals. Author Video: An author video summary of this article is available.